Biodegradable Microplastics: Environmental Fate and Persistence in Comparison to Micro- and Nanoplastics from Traditional, Non-Degradable Polymers - Paolo Costa; Maximilian Lackner (Macromol, 2025)
The escalating production of virgin plastics has resulted in an unprecedented generation of microplastics (MPs), posing significant environmental and health risks. Biodegradable plastics have emerged as an alternative, but their degradation also releases microplastic-sized particles, referred to as biodegradable microplastics (BMPs). This review evaluates the current understanding of BMPs, focusing on their environmental fate, degradation kinetics, and comparative persistence relative to conventional MPs. The degradation process of biodegradable plastics involves sequential abiotic and biotic mechanisms, with factors such as polymer chemistry, geometry, and environmental conditions influencing BMPs’ formation and mineralization. Studies highlight the temporal advantage of BMPs, which exhibit significantly shorter lifetimes than traditional MPs; however, their environmental impact remains context-dependent, particularly in soil and aquatic systems. Despite promising results under controlled conditions, challenges in standardizing biodegradation assessments and discrepancies between laboratory and real-world scenarios complicate evaluations of the temporal fate and the effects of BMPs. This work underscores the need for long-term studies and improved modeling approaches to accurately predict BMP behavior and mitigate their ecological impact. Poly(hydroxyalkanoates) are a class of fully biodegradable polymers that do not leave behind persistent microplastics. Biodegradable plastics should be prioritized over non-degradable, traditional polymers, as they can replace them in a large fraction of applications, yet with a significantly reduced footprint and without leaving behind persistent micro- and nanoplastics. They can also be recycled.